p53 mutation and deletion contribute to tumor immune evasion - Liu, Siyang; Liu, Tianyao; Jiang, Jiaxuan; Guo, Hongqian; Yang, Rong (Frontiers in Genetics, 2023)
TP53 (or p53) is widely accepted to be a tumor suppressor. Upon various cellular stresses, p53 mediates cell cycle arrest and apoptosis to maintain genomic stability. p53 is also discovered to suppress tumor growth through regulating metabolism and ferroptosis. However, p53 is always lost or mutated in human and the loss or mutation of p53 is related to a high risk of tumors. Although the link between p53 and cancer has been well established, how the different p53 status of tumor cells help themselves evade immune response remains largely elusive. Understanding the molecular mechanisms of different status of p53 and tumor immune evasion can help optimize the currently used therapies. In this context, we discussed the how the antigen presentation and tumor antigen expression mode altered and described how the tumor cells shape a suppressive tumor immune microenvironment to facilitate its proliferation and metastasis.